Activities of the healthcare team for women who smoke during pregnancy and the puerperium - Carolina de Castilhos Teixeira; Amália de Fátima Lucena; Isabel Cristina Echer (Universidade de São Paulo, 2014)
OBJECTIVE: to identify activities developed by the healthcare team for pregnant and postpartum women who smoke.METHOD: cross-sectional study with a sample of 135 healthcare team members who assist pregnant and postpartum women in a university hospital located in southern Brazil. The data was collected using questionnaires and analyzed using the Statistical Package for Social Sciences software.RESULTS: 76 (56.3%) staff members reported that they always addressed smoking cessation; however, the approach occurred in only two periods of the hospitalization and/or prenatal consultations, not including family members. In regard to the effectiveness of their actions, the health team assessed it as fair or poor, and mentioned the need for updating knowledge regarding this issue.CONCLUSIONS: the health team did not perform the approach as recommended by the tobacco control guidelines, requiring training to offer a qualified and efficient intervention.